Creative Turns in the Use of Industrial Resources for Heritage Tourism in Taiwan. Issue 3 (1st October 2016) - Wu, Tsung-Chiung (Emily); Wall, Geoffrey; Yu, Wan-Chen (Vinney)
ABSTRACT: In heritage tourism, traditional industrial production may be transformed through creative processes that reposition the resources to produce novel tourist experiences. This study examines the transformation of salt resources in Taiwan from the production of a tangible to an experiential product. Formerly, the production of salt as an industrial product resulted in the creation of distinctive landscapes and livelihoods. The decline of this industry has been followed by the creation of new heritage values through innovative presentation of cultural relicts and consumption of recreational experiences in tourism. To probe the receptivity of this radical change in resource use, a quasi-experimental approach is used to examine how the repositioned industrial legacy meets the expectations of heritage tourists. Hybrid combinations of presentation schemes (theme, programming, and design) reveal creative turns in the use of industrial resources for the production of tourist experiences. Although there is diversity among the preferences of visitors, participatory experiences are generally preferred to passive viewing of relict landscapes.